Correction: AlMotwaa, S.M.; Al-Otaibi, W.A. Gemcitabine-Loaded Nanocarrier of Essential Oil from Pulicaria crispa: Preparation, Optimization, and In Vitro Evaluation of Anticancer Activity. Pharmaceutics 2022, 14, 1336 - Sahar M. AlMotwaa; Waad A. Al-Otaibi (Pharmaceutics)
Error in Figure [...]